Improving Students' Creative Thinking Ability Through Independent Learning and Intellectual Intelligence - Ferdinand Salomo Leuwol; Lindawati Lindawati; Mokhammad Wahyudin; Robby Tanod Mamusung; Budi Mardikawati (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the low ability of students' creative thinking. The purpose of this study was to examine and analyze the Improvement of Students' Creative Thinking Ability Through Independent Learning and Intellectual Intelligence. This research uses a quantitative approach with a survey method. The sampling technique used purposive sampling of 100 students. The instruments used are tests and questionnaires. The data analysis technique used is the classical assumption, correlation analysis, and multiple linear regression analysis including hypothesis testing T test, F test and R2 test. The results of this study indicate: 1) Learning Independence has a positive and significant effect on Students' Creative Thinking Ability, 2) Intellectual Intelligence has a positive and significant effect on Student Creative Thinking Ability, and 3) Learning Independence and Intellectual Intelligence have a positive and significant effect on Student Creative Thinking Ability. The findings of this study indicate the importance of learning independence and intellectual intelligence in improving students' creative thinking skills.